Experimental studies on cell and gene therapies for retinal dystrophies with a particular focus on ABCA4 retinopathies - Ścieżyńska, Aneta; Oziębło, Dominika; Ołdak, Monika (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Retinal dystrophies lead to gradual irreversible vision deterioration. The ABCA4 retinopathies constitute an important group of retinal dystrophies. However, there are no effective therapies available for this group of diseases. Yet, with the advent of molecular therapies, the development of prospective therapeutic approaches seems feasible. The paper summarizes recent advances in gene and cell therapy that may be implemented in retinal dystrophies, especially in ABCA4 -associated diseases.